A Comprehensive Social Pedagogical Approach to Solving the Problems of Education, Upbringing, Development - Feruza, Muhammadiyeva (European Journal of Life Safety and Stability (2660-9630), 2021)
It is known that each science is distinguished by a system of knowledge based on the subject of study of this science. The knowledge system of science is reflected in its concepts and categories. Concept-reality occurs in the process of knowing the universe. Because reality is variable, concepts also tend to change and evolve dynamically. In other words, concepts change depending on historical situation and living conditions.